Infamous - Spencer, Minerva (Spencer, Minerva. Rebels of the Ton, 2021)
"A mean girl reformed . . .Once the reigning beauty of her social set, Celia--whom the newspapers dubbed Lady Infamous--has fallen on hard times and is practically destitute, her reputation in shreds. When Celia is forced to attend a society wedding as a companion to an elderly guest, she must confront the clique she once commanded; the gentleman she'd once hoped to marry--who is now wed to a girl Celia relentlessly taunted; and the powerful man who ruined her life a decade before--and is threatening to do so again. . . .A hero transformed . . .Then there is Richard, the studious boy Celia used to ridicule, who is now gorgeous, wealthy, and and more than-a-little famous. As a youth, Richard was infatuated with Celia. He still seems intrigued, but Celia has acquired a shocking secret along with her hard-won humility. Will it put an end to the love blossoming between them? Does she have the courage to find out?"--FantasticFiction.com.